Repression and Expression of S exuality in Thomas Hardy’s Tess of the d’Urbervilles: the Paradox and Virtue of Censorship - Thierry Goater (Revue LISA)
Throughout his novelistic career, Thomas Hardy had to face various forms of censorship, to such an extent that one can wonder if they did not contribute to his giving up writing fiction. However, censorship is a complex and ambiguous phenomenon. If there was censorship in literature during the Victorian period, it was mainly more the effect of pervading Puritanism, voiced by leagues of virtue or carried out by editors and publishers, than the result of legal machinery. Literature was only indirectly affected by censorship: editors ensured that ‘morality’ and the sensibility of ‘fragile’ readers were respected. Indeed in the 19th century many novels were published serially in magazines aimed at families, women and children. On the other hand, the strategies devised by authors to circumvent censorship were often aesthetically fruitful. One could even wonder whether, paradoxically, Victorian censorship did not favour the expression of the ‘forbidden’ rather than its repression, whether it did not reveal more than it tried to conceal. This paper will analyse all these issues through the question of sexuality in Tess of the d’Urbervilles, one of Hardy’s last novels that was given a particularly rough ride by publishers.